A methodology for low-speed broadband rotational energy harvesting using piezoelectric transduction and frequency up-conversion. (15th April 2017) - Fu, Hailing; Yeatman, Eric M.
Abstract: Energy harvesting from vibration for low-power electronics has been investigated intensively in recent years, but rotational energy harvesting is less investigated and still has some challenges. In this paper, a methodology for low-speed rotational energy harvesting using piezoelectric transduction and frequency up-conversion is analysed. The system consists of a piezoelectric cantilever beam with a tip magnet and a rotating magnet on a revolving host. The angular kinetic energy of the host is transferred to the vibration energy of the piezoelectric beam via magnetic coupling between the magnets. Frequency up-conversion is achieved by magnetic plucking, converting low frequency rotation into high frequency vibration of the piezoelectric beam. A distributed-parameter theoretical model is presented to analyse the electromechanical behaviour of the rotational energy harvester. Different configurations and design parameters were investigated to improve the output power of the device. Experimental studies were conducted to validate the theoretical estimation. The results illustrate that the proposed method is a feasible solution to collecting low-speed rotational energy from ambient hosts, such as vehicle tires, micro-turbines and wristwatches. Highlights: A topology to harvest low-frequency broad-band rotational energy is studied. Different configurations were considered; arrangement (a)-repulsive was the best. Theoretical analysis shows the harvester has a wide bandwidth at low frequency. The ripples of output power are related to the beam's natural frequency. Experimental results show a good performance (over 20 μW) from 15 Hz to 35 Hz.